2014
DOI: 10.1002/2014jd022219
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate modeling over China with COSMO‐CLM: Performance assessment and climate projections

Abstract: This study presents the results of high-resolution (0.125°) climate simulations over a Chinese area performed with an optimized configuration of the regional climate model COSMO-CLM, driven by ERA-Interim Reanalysis over the period 1979-2011 and by the output of the global model CMCC-CM (resolution 0.75°) over the period 1979-2100. The main aim of this work was to analyze the capabilities of COSMO-CLM to describe the climate of China in the recent past; validation revealed a good improvement in reproducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…However, Chen and Sun [2009] suggested that the CMIP3 multimodel ensemble projected that there would be a decrease in the Xinjiang province in northwest China. In addition, the projection by Bucchignani et al [2014] with COSMO-CLM under the RCP4.5 scenario shows a similar pattern of winter precipitation changes but nearly an opposite changing pattern of summer precipitation changes. Therefore, large uncertainties still exist in future precipitation projections in China [Gao et al, 2012].…”
Section: Projections Of Total Precipitationmentioning
confidence: 76%
“…However, Chen and Sun [2009] suggested that the CMIP3 multimodel ensemble projected that there would be a decrease in the Xinjiang province in northwest China. In addition, the projection by Bucchignani et al [2014] with COSMO-CLM under the RCP4.5 scenario shows a similar pattern of winter precipitation changes but nearly an opposite changing pattern of summer precipitation changes. Therefore, large uncertainties still exist in future precipitation projections in China [Gao et al, 2012].…”
Section: Projections Of Total Precipitationmentioning
confidence: 76%
“…Hence to assess their simulation in the regional climate model and the possible changes in these systems under global warming scenario is very crucial. Bucchignani et al (2014) [14] assessed the performance of COSMO-CLM over China. Panitz et al (2014) [15] have analysed COSMO-CLIM simulations over CORDEX-Africa domain.…”
Section: Introductionmentioning
confidence: 99%
“…The PRECIS simulation domain covered China with a 0.22° × 0.22° spatial resolution. Based on the geographical features of temperature changes over China and previous related studies (Bucchignani et al, ; Li et al, , ; Luo et al, ), the contiguous domain of China was divided into seven subregions, including Northwest China (NW), North Central China (NC), Northeast China (NE), Tibetan Plateau (Tibet), Southwest China (SW), Southeast China (SE), and Yangtze (YZ). As shown in Figure , the subregions are typically used in weather‐ and climate‐related studies in China because of climatic similarities within every subregion.…”
Section: Methods and Data Setsmentioning
confidence: 99%